Modification of inhibitory control and craving through transcranial direct current stimulation as an add-on treatment for substance use disorder: protocol for a randomized controlled study : study protocol - Vollstädt-Klein, Sabine; Türkmen, Cagdas; Grundinger, Nadja; Wieland, Alfred; Aggensteiner, Pascal; Stock, Ann-Kathrin; Stein, Maria; Moggi, Franz; Bublatzky, Florian; Kiefer, Falk; Link, Tobias; Gerhardt, Sarah (BMC Psychology, 2025)
Substance use disorders (SUDs) remain a prevalent public health issue characterized by a substantial disease burden and high relapse rates. The aim of this planned project is to investigate the optimal electrode placement and polarity of transcranial direct current stimulation (tDCS) to reduce cognitive deficits and substance craving in individuals with SUDs, thereby contributing to improved treatment outcomes, including longer abstinence periods and reduced substance use after relapse.
Online veröffentlicht: 13. Oktober 2025
Gesehen am 08.01.2026